Estrogen receptors α and β in the central amygdala and the ventromedial nucleus of the hypothalamus: Sociosexual behaviors, fear and arousal in female rats during emotionally challenging events - Le Moëne, Olivia; Stavarache, Mihaela; Ogawa, Sonoko; Musatov, Sergei; Ågmo, Anders (Behavioural brain research, 2019)
•Estrogen receptor α is essential for female sexual behaviors.•Activation of estrogen receptor β in the central amygdala reduces anxiety.•Estrogen receptor β modulates arousal level.•The use of a seminatural environment highlights the context-dependent role of ERs. Estrogens receptors (ER) are involved in several sociosexual behaviors and fear responses. In particular, the ERα is important for sexual behaviors, whereas ERβ modulates anxiolytic responses. Using shRNA directed either against the ERα or the ERβ RNAs (or containing luciferase control) encoded within an adeno-associated viral vector, we silenced these receptors in the ventromedial nucleus of the hypothalamus (VMN) and the central amygdala (CeA). We exposed ovariectomized female rats, sequentially treated with estradiol benzoate and progesterone, to five stimuli, previously reported to elicit positive and negative affect. The subjects were housed in groups of 4 females and 3 males in a seminatural environment for several days before hormone treatment. We analyzed the frequency of a large number of behavior patterns. In addition, we performed analyses of co-occurrence in order to detect changes in the structure of behavior after infusion of the vectors. Silencing the ERα in the VMN disrupted lordosis and showed some anxiolytic properties in aversive situations, whereas silencing of the ERβ in this structure had no effect. This was also the case after silencing the ERα in the CeA. Silencing of the ERβ in this structure increased risk assessment, an expression of anxiety, and increased olfactory exploration of the environment. We hypothesize that the ERβ in the CeA has an important role in the well-established anxiolytic effects of estrogens, and that it may modulate arousal level. Furthermore, it seems that the ERα in the VMN is anxiogenic in aversive or threatening situations, in agreement with other studies.